The growing trend for no primary surgery in colorectal cancer. (27th July 2021) - Peponis, Thomas; Stafford, Caitlin; Cusack, James; Cauley, Christy; Goldstone, Robert; Berger, David; Bordeianou, Liliana; Kunitake, Hiroko; Francone, Todd; Ricciardi, Rocco
Abstract: Aim: In colorectal cancer (CRC), surgery of the primary site is commonly curative. Our aim was to determine estimates of 'no surgery' for primary CRC while identifying common reasons for no surgery. Method: We identified all patients with a diagnosis of colorectal adenocarcinoma from the National Cancer Database between January 2004 and December 2016. Then, we identified patients who did not undergo surgery on the primary tumour and their demographic, tumour and institutional characteristics. Kaplan–Meier and logistic regression analyses were used to evaluate specific factors associated with overall survival as related to no surgery and recommendations against operative management. Results: A total of 1, 208, 878 patients with CRC were identified, 14.5% of whom had no surgery of the primary cancer. No surgery was more common in rectal cancer than in colon cancer. Despite a steady incidence of CRC diagnoses, the likelihood of no surgery grew by 170% over the study period. Metastatic disease was noted in 53.7% of the no surgery cohort. Nine per cent of the no surgery patient cohort received a recommendation against surgery despite the absence of metastatic disease, 7.5% refused surgery and only 2% underwent palliative surgery. On multivariable analysis, patients who were not recommended to have surgery were more likely to be older, uninsured, comorbid and receive care at a single hospital. The no surgery patients had significantly lower overall survival. Conclusion: A substantial proportion of patients with CRC do not have surgery. Interventions aimed at expanding access and promoting second opinions at other cancer hospitals might reduce the growing rate of no surgery in CRC.